Pelatihan Peningkatan Kompetensi Guru Dalam Pembuatan Karya Ilmiah Pada SD Inpres Dulanpokpok - Ardhiansyah Mualo; Hasan Basri (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Along with the times, human development has also increased, not only the environment and needs, but also has an impact on the level of education. If in the past our parents' education only reached high school or college because of economic limitations, access to transportation, and access to information, then it's different from now where we can easily get all of these accesses, besides that there's no word not being able to continue our education. to a higher level because at this time the opportunity to get a scholarship is very wide open. For this reason, education is the main thing to deal with the current rapid development of the times and technology. In addition to providing quality education in accordance with competence, Higher Education also provides additional knowledge to improve competence by pouring it into the form of scientific work. Scientific work is very important for teachers, because it can function as an addition to insight or disseminate knowledge. Writing scientific papers helps teachers become more productive in reading and writing, practicing integrating various references and presenting them well, broadening knowledge, and providing intellectual satisfaction. Therefore, the level of professionalism of teachers needs to be increased and teachers can carry out their duties in a trained manner. With scientific work it is expected to increase competence so that teachers become professional in carrying out their duties and responsibilities. Furthermore, teachers who can improve their professional quality must be rewarded with promotions/grades. SD Inpres Dulanpokpok is one of the schools that really supports increasing teacher competence in making scientific work, the location of this school is approximately 7 km from the center of Fakfak city but does not close itself to synergizing with the Fakfak State Polytechnic to carry out teacher competency development. However, the distance that can be said is quite far so that the service activities carried out by the Fakfak State Polytechnic and surrounding universities did not reach SD Inpres Dulanpokpok.